Estimate of genetic parameters in a progeny test of Pinus radiata D. Don in Basque Country - Arregui, A.; Espinel, S.; Aragones, A.; Sierra, R. (Forest Systems, 1999)
Genetic parameters were estimated for growth, form and Diplodia pinea susceptibility in a six-year-old progeny trial containing 30 open pollinated families of Pinus radiata D. Don selected plus trees. Individual heritabilities were moderate for height, diameter and susceptibility of Diplodia pinea, but low for stem straightness and brach diameter. Branch angle showed moderate-low heritability. Height and diameter were positively correlated. Growth traits had negative correlation with susceptibility of Diplodia pinea, so it is possible to achieve simultaneous improvements in both growth and Diplodia resistence.